2017
DOI: 10.1371/journal.pone.0185319
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial αENaC contributes to vascular endothelial function in vivo

Abstract: The Epithelial Sodium Channel (ENaC) is a key player in renal sodium homeostasis. The expression of α β γ ENaC subunits has also been described in the endothelium and vascular smooth muscle, suggesting a role in vascular function. We recently demonstrated that endothelial ENaC is involved in aldosterone-modulated endothelial stiffness. Here we explore the functional role of the endothelial αENaC subunit in vascular function in vivo. Compared to littermates, mice with conditional αENaC subunit gene inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 29 publications
(49 reference statements)
11
50
4
Order By: Relevance
“…The reason for this selection is because we found that dilation responses were relatively consistent across arteries of slightly different diameters and magnitudes of preconstriction at each flow rate (Fig. 1), and these response curves were similar to those found in many previous studies using stepped increases in flow in mouse mesenteric arteries (Loufrani et al 2002;Ohlmann et al 2005;Sennoun et al 2009;Priou et al 2010;Leonetti et al 2013;Tarjus et al 2017;Xu et al 2018), and more robust than found in some studies (Douglas et al 2008;Besnier et al 2018). Although the calculated shear stress was different between arteries at the start of flow (Initial Shear Stress), due to variation in diameters after preconstriction with phenylephrine, the final calculated shear stress (Final Shear Stress) values had much less variability as indicated by the smaller SEM ("Control" arteries in Tables 2 and 3).…”
Section: Limitationssupporting
confidence: 84%
See 1 more Smart Citation
“…The reason for this selection is because we found that dilation responses were relatively consistent across arteries of slightly different diameters and magnitudes of preconstriction at each flow rate (Fig. 1), and these response curves were similar to those found in many previous studies using stepped increases in flow in mouse mesenteric arteries (Loufrani et al 2002;Ohlmann et al 2005;Sennoun et al 2009;Priou et al 2010;Leonetti et al 2013;Tarjus et al 2017;Xu et al 2018), and more robust than found in some studies (Douglas et al 2008;Besnier et al 2018). Although the calculated shear stress was different between arteries at the start of flow (Initial Shear Stress), due to variation in diameters after preconstriction with phenylephrine, the final calculated shear stress (Final Shear Stress) values had much less variability as indicated by the smaller SEM ("Control" arteries in Tables 2 and 3).…”
Section: Limitationssupporting
confidence: 84%
“…1A in [Looft-Wilson et al 2008]) and the deep constriction allows observation of a larger magnitude flow-induced vasodilation response. Moreover, use of this agonist and this magnitude of preconstriction is typical when examining flow-induced dilation in these arteries (Loufrani et al 2002;Sennoun et al 2009;Tarjus et al 2017;Besnier et al 2018;Xu et al 2018). This phenylephrine dose results in eNOS phosphorylation changes (Looft-Wilson et al 2013), and it is possible that these phosphorylation changes are maximal.…”
Section: Limitationsmentioning
confidence: 99%
“…11,14,15 A lack of effect on baseline blood pressure of endothelial ENaC was corroborated by recent data showing no difference between wild type mice and mice with endothelial deletion of α-ENaC. 16 These data suggest that the observed acute blood pressure-lowering effect exerted by amiloride was not caused by eNOS-derived NO formation in the endothelium after blocking of EnNaC but rather caused by an effect on the heart which was blunted in eNOS −/− mice. Previous data have shown that amiloride has a negative chronotropic action on isolated sinoatrial node 17 and in dog heart.…”
Section: Discussionmentioning
confidence: 71%
“…Data are shown as means ± SEM; *P < 0.05, † P < 0.01, ‡ P < 0.001 contrast to predicted from single cells data. 16 Long-term amiloride in fat-fed mice improved endothelial function and reduced aortic stiffness in mice without affecting blood pressure. 20 Amiloride has vasodilatator properties in humans 21 and in dogs 22 and the compound relaxes aortic rings and increases cGMP in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Now it is obvious that ENaC is expressed in a variety of different tissues where it fulfills diverse functions. In particular, ENaC was identified in the vascular endothelium, where it controls endothelial nanomechanics [50,167]. ENaC, like many other ion channels, is linked to cytoskeletal components and these interactions are used for mechanotransduction [51,78,118,185].…”
Section: Mechanosensitive Channels In the Endotheliummentioning
confidence: 99%